จัดสวัสดิการให้พนักงานอย่างไรให้ถูกหลักภาษีอากร - เจนศิริศักดิ์ ศิริรัตน์; จันทรุกขา ศุภกัญญา (Journal of Business, Innovation and Sustainability (JBIS), 2012)
บทความวิชาการนี้มีวัตถุประสงคเพื่อกระตุนใหบุคลากรที่เกี่ยวของกับการจางงาน ทั้งนายจาง ลูกจาง หรือ บุคลากรฝายทรัพยากรมนุษย โดยเล็งเห็นถึงความสําคัญของการศึกษาและวางแผนการจัดสวัสดิการที่สามารถจูงใจ ลูกจางใหมและลูกจางเดิมไดอยางจริงจัง พรอมๆ กับการพิจารณาถึงผลประโยชนสูงสุดที่ลูกจางและองคการจะไดรับใน ประเด็นของภาษีอากรตามประมวลรัษฎากร บทความนี้ไดศึกษาและรวบรวมขอมูลจากงานวิจัยที่ผานมา กฎหมายที่ เกี่ยวของ และหนังสือตอบขอหารือของกรมสรรพากรตั้งแตเดือนมกราคม พ.ศ. 2550 ถึงเดือนกันยายน พ.ศ. 2554 ที่ เกี่ยวของกับการจัดสวัสดิการเพื่อประโยชนแกลูกจางและนายจาง ทั้งในดานภาษีเงินไดบุคคลธรรมดาและภาษีเงินไดนิติ บุคคล เนื่องจากการจัดสวัสดิการในรูปแบบตางๆ อาจไดรับการยกเวนและลูกจางไมตองนํามาถือเปนเงินไดพึงประเมิน ในขณะที่สวัสดิการบางประเภท ลูกจางอาจจําเปนตองนํามารวมเปนเงินไดพึงประเมินตามมาตรา 39 แหงประมวล รัษฎากร เชนเดียวกับองคการที่จัดสวัสดิการใหกับลูกจาง ก็ตองพิจารณาวาสวัสดิการเหลานั้นอาจจะถือเปนรายจายของ องคการ หรืออาจจะถือเปนรายจายตองหามตามมาตรา 65 ตรี แหงประมวลรัษฎากรก็ได ที่สําคัญที่สุดคือ นายจาง จําเปนที่จะตองจัดสวัสดิการใหเขากับองคประกอบที่กฎหมายกําหนดไว เพื่อประโยชนสูงสุดทางภาษีอากร ดังนั้น การศึกษาถึงกฎหมาย ขอบังคับ ขอหารือ และขอยกเวนตางๆ จึงเปนสิ่งจําเปนที่ผูที่เกี่ยวของในองคการ ควรศึกษาและ ทําความเขาใจอยางถองแท ทั้งนี้ เพื่อประโยชนของลูกจางและองคการ The purpose of this paper was intended to encourage personnel-related employment as employers, employees or human resource personnel to recognize the importance of studying and planning in welfare that can attract new employees and existing employees seriously. With consideration to the interests of employers and organizations will be on issues of taxation under the Revenue Code. This paper studied and collected information from past research, relevant laws and discussed letters of the Department of Revenue from January 2550 until September 2554 which related to welfare benefits for employees and employers in terms of Personal Income Tax and Corporate Income Tax. Due to the various forms of welfare, would be exempted and shall not be considered as assessable income. Nevertheless, employees have to include some benefits as assessable income under section 39 of the Revenue Code. As well as organizations that provide welfare to employees, these benefits may be considered as expenses of the organization or expenditure prohibited by Section 65 Ter of the Revenue Code. The most important is the welfare in order to get the most out of tax. It is necessary that employers must provide welfare with elements by the law. Therefore, the study of the laws, regulations, discussions and these exceptions are essential that stakeholders in organizations should study and understand clearly for benefits of both employees and organizations. DOI: http://dx.doi.org/10.14456/becj.2012.13